Comorbidity and polypharmacy among women living with HIV in British Columbia. (1st December 2019) - Donaldson, Mira A.; Campbell, Amber R.; Albert, Arianne Y.; Borhani, Mahtab; Nesbitt, Ariel; Côté, Hélène C.F.; Maan, Evelyn J.; Pick, Neora; Murray, Melanie C.M.
Abstract : Objective: To characterize comorbid disease and medication burden among women living with HIV (WLWH) in British Columbia (BC), Canada. Design: We examined baseline data from 267 WLWH and 276 HIV-negative women, aged at least 19 years, enrolled in the Children and Women: Antiretrovirals and Markers of Aging (CARMA) cohort. Methods: Self-reported demographic, medical condition, medication, vitamin, and substance exposure data were collected at baseline CARMA study visits. We considered conditions with appropriate concomitant medications to be 'treated'. Wilcoxon rank-sum and Fisher's exact tests compared continuous and categorical variables between WLWH and HIV-negative women. Number of diagnoses, prescribed medications (excluding HIV/antiretrovirals), vitamins, and prevalence of depression/anxiety/panic disorder were compared using negative binomial and logistic regressions for continuous and binary variables, respectively. Results: WLWH were younger [median, interquartile range (IQR) 39.9, 33.6–46.9 vs. 43.6, 31.8–54.6 years; P  = 0.01], attained lower education (40.5 vs. 69.6% college/university; P  < 0.001), and more often currently smoked tobacco (47.9 vs. 31.9%; P  < 0.001) or had income less than $15 000/year (49.0 vs. 43.1%; P  < 0.001). Although younger, and despite omitting HIV infection, WLWH had a greater number of diagnoses (incidence rate ratio, 95% confidence interval 1.58, 1.38–1.81; P  < 0.001), and more depression/anxiety/panic disorder vs. controls (odds ratio, 95% CI 1.86, 1.22–2.83; P  = 0.004). Our model predicts that with mean BMI (26.3), WLWH and HIV-negative peers would have two comorbid diagnoses by age 30 and 60, respectively. Conclusions: WLWH living in BC have more comorbid illness earlier in life than their HIV-negative peers, and have very high rates of depression/anxiety/panic disorder. Addressing mental health and comorbid conditions is essential to improving health outcomes among WLWH. Abstract : Supplemental Digital Content is available in the text